Le choix de l’observation pour l’étude des pratiques enseignantes - Marc Bru (Recherches en Éducation)
The choice of observation to study teaching practices is widely recognized. Nevertheless, it arouses a critical look; without question it, it allows to continue the debate in order to locate objectives and issues. The article attempts to reactivate some of the elements of this debate all the more necessary. On the one hand, a case design tools methodology sometimes dominates the research training. On the other hand, social and institutional demands are often waiting to see finally identified best practices. In addition, epistemological options are quick to confine the observation in a kind of strict objectivism. This results in the tendency to define categories and establish oppositions on the latter, which ultimately reduces and damages research perspectives.